Desenvolvimento Tecnológico e Avaliação da Atividade Antimicrobiana de Micropartículas de Polilisina e de Nanocápsulas contendo óleo essencial de Melaleuca Alternifolia Cheel (Myrtaceae) - Mirante, Daiane Cristine (2015)
The development of antimicrobial agents is one of the most important advances in the therapeutic area due to microbial resistance, causing problems to public health, with serious economic, social and political implications. Thus, this study aimed to the technological development of microparticles of biopolymer poly-L-lysine (PLL) and polymeric nanocapsules containing essential oil of Melaleuca alternifolia Cheel uncoated or coated with PLL. The microparticles were obtained by the spray drying technique with a yield of 42.4%. The nanocapsules were prepared by interfacial deposition technique of a preformed polymer. The nanocapsules showed average nanometer diameter (160-200 nm), polydispersity index of less than 0.25 and negative zeta potential for nanocapsules poly(caprolactone) (PCL) (-39.8 mV) and positive for the nanocapsules of PLL (+17, 75 mV), indicating that there was an electrostatic adsorption interaction between PCL and PLL. An analytical method was developed and validated by UV-vis pectrophotometry in order to enable a reliable determination of encapsulation efficiency (EE). This method showed specificity, linearity, precision, detection and quantification satisfactory limits according to current recommendations. The EE was 99.86%. The antimicrobial activity of micro systems and nanocapsules was evaluated, containing PLL against the microorganisms, E. coli S. aureus, S. pyogenes, P. aeruginosa and C. albicans. The results demonstrate that the incorporation of the essential oil of M. alternifolia in the nanostructured system developed has been able to increase their antibacterial activity. The microparticles and nanocapsules, can, in the future, be promising antimicrobial agents, promoting the development of an effective therapeutic alternative and more effective at lower doses.